2022
DOI: 10.1108/jcms-12-2021-0041
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning with small and big data of symmetric volatility information for predicting daily accuracy improvement of JKII prices

Abstract: PurposeThe purpose of this paper is to predict the daily accuracy improvement for the Jakarta Islamic Index (JKII) prices using deep learning (DL) with small and big data of symmetric volatility information.Design/methodology/approachThis paper uses the nonlinear autoregressive exogenous (NARX) neural network as the optimal DL approach for predicting daily accuracy improvement through small and big data of symmetric volatility information of the JKII based on the criteria of the highest accuracy score of testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Because choosing this period is optimal for collecting the big balance data sheet of JKII's financial data from Investing database to use it for extracting the largest possible hidden knowledge from it, which helps to predict daily precision improvement of JKII prices using data mining. The four attributes of the symmetric volatility framework are used as inputs (CP, LP, HP and OP) based on studies on predicting stock markets indices by Nayak et al (2015), Khedr and Yaseen (2017), Vijh et al (2020), Ampomah et al (2021) and Ledhem (2022). Although the output layer comprises a single target to be predicted, which is the daily actual JKII prices.…”
Section: Big Data Collectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Because choosing this period is optimal for collecting the big balance data sheet of JKII's financial data from Investing database to use it for extracting the largest possible hidden knowledge from it, which helps to predict daily precision improvement of JKII prices using data mining. The four attributes of the symmetric volatility framework are used as inputs (CP, LP, HP and OP) based on studies on predicting stock markets indices by Nayak et al (2015), Khedr and Yaseen (2017), Vijh et al (2020), Ampomah et al (2021) and Ledhem (2022). Although the output layer comprises a single target to be predicted, which is the daily actual JKII prices.…”
Section: Big Data Collectionmentioning
confidence: 99%
“…Despite the existence of numerous studies on the prediction of conventional stock markets, to the best of the authors’ knowledge, there is a limited number of studies that focus on the prediction of the Islamic stock market using ANNs. In a recent study, Ledhem (2022) predicted the prices of the JKII using ANNs. His findings indicated that ANNs are highly suitable for predicting stock market prices.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations